A checklist of the dragonflies from the North-Western of Isiboro-Sécure Indian Counntry and National Park, Bolivia - Pessacq, Pablo (2015)
The Isiboro-Secure Indian Country and National Park is located in central-western Bolivia, in the departments of Beni and Cochabamba. The Park includes about 12,363 km² of Yunga rainforest in the Bolivian Amazon. This is the first entomological cheklist and taxonomic study within the park. Twentythree species of odonata are listed (15 Zygoptera and 18 Anisoptera species). Five new records for the countryt and at least three probable new species are recorded.